2'‐(1,3‐Dithiolan‐2‐ylidene)‐4'‐(1,3‐dithiol‐2‐ylidene)spiro[1,3‐dithiole‐2,5'‐(4'H‐5',6'‐dihydro‐1',3'‐dithiapentalene)], the Self‐Condensation Product of an Extended Tetrathiafulvalene Derivative - Meziere, C.; Salle, M.; Fourmigue, M. (Acta crystallographica. Section C, Crystal structure communications, 1998)
SiO2-​gel treatment of the extended tetrathiafulvalene derivative 2,​3-​bis(1,​4-​dithiafulven-​6-​yl)​-​6,​7-​dihydrotetrathiafulvalene, bearing two 1,​4-​dithiafulven-​6-​yl groups in vicinal positions, afforded the title compound, C14H10S8, as a cyclization product. While one dithiafulvenyl group is still conjugated with the tetrathiafulvalene moiety, the other one gives rise to a strongly folded 1,​3-​dithiole group linked to the molecule through a spiro-​C atom. Two short nonbonding intramolecular 1,​5-​S···S contacts are also identified in the title compound.